Descriptive Study on Allocation of Zakat Distribution Based on Maqashid Syariah - Setiyadi, Amin; Mahri, A. Jajang W.; Juliana, Juliana; Sutjipto, Hady (PT. Student Rihlah Indonesia, 2025)
This study aims to describe the distribution of zakat by BAZNAS Bandung Raya based on the perspective of maqashid sharia, which includes five main dimensions: protecting religion, soul, mind, descendants, and property. The method used is a descriptive-quantitative approach with data collection through questionnaires to 62 amil zakat from five BAZNAS in the Bandung Raya area. The results of the study indicate that in general the distribution of zakat is in the high category, with the largest allocation in the aspect of protecting descendants and mind through education programs and social assistance. The zakat distribution model is carried out in two forms, namely consumptive and productive. The implications of this finding emphasize the importance of reformulating the zakat distribution strategy to be more proportional to all dimensions of maqashid sharia, as well as the need to strengthen institutions and use information technology in zakat management. This study provides theoretical contributions to the study of Islamic economics and becomes a practical reference for zakat institutions to increase the effectiveness and social impact of zakat distribution in society.